The challenges of using online surveys - Carvalho, João M. S. (2022)
In recent years, the exponential increase in the number of researchers and research projects around the world has posed great challenges to the possibility of obtaining sufficiently representative samples in responses to online surveys. Thus, with the possibility of using the online route to reach potential participants in studies, researchers still have the need to justify their approach, in order to remain faithful to the scientific method. This case addresses these issues, as well as presents the most common challenges that researchers face when proposing to use the online survey method. These challenges range from the original design of the study to the way the questions are formulated and presented online to the respondents, including the difficulty in obtaining the correct database and the appropriate choice of the statistical approach in the analysis of the data.